PEPTIDYL TRANSFERS IN GRAMICIDIN S BIOSYNTHESIS FROM ENZYME-BOUND THIOESTER INTERMEDIATES - Gevers, Wieland (1969)
The biosynthesis of the peptide antibiotic gramicidin S involves successive peptidyl transfer reactions between intermediates bound in thioester linkages to two active enzyme fractions, I and II. Fraction II activates and recemizes phenylalanine, and then initiates peptidyl transfer by catalyzing a reaction between the carboxyl group of D-phenylalanine, bound to an enzymic sulfhydryl group, and the free imino group of L-proline, one of four L-amino acids all linked by their carboxyl functions to separate sulfhydryl groups on fraction I. Successive reactions of this type in the active centers of the multienzyme complex of fraction I lead to the formation of thioester-bonded nascent peptide chains and, ultimately, of the antibiotic product.